(untitled) (Praxis Educativa, 2024)
This article reflects on the living and teaching work conditions of rural teachers during the time of the COVID19 pandemic in our country. Some results of a completed research project called “Rural education and education of youth and adults in the province of La Rioja” are included. A case study in the Chilecito Department” with a workplace in the Department of Education and Health Sciences, National University of Chilecito between 2019 and 2022. This research aimed to know the characteristics of educational practices in rural education and of young people and adults in the province of La Rioja, particularly in the Chilecito Department. We understand that in the configuration of these practices, the policies intended for these modalities of the educational system are woven in light of the institutional configurations and the trajectories of the subjects involved.